2019
DOI: 10.1002/jcla.22858
|View full text |Cite
|
Sign up to set email alerts
|

SNPs in LncRNA genes are associated with non‐small cell lung cancer in a Chinese population

Abstract: BackgroundIt has indicated that single nuclear polymorphisms (SNPs) in the regions encoding non‐coding transcripts are associated with lung cancer susceptibility. In a previous microarray study, we identified 13 differentially expressed long non‐coding RNAs (lncRNAs) in non‐small cell lung cancer (NSCLC) and associations of SNPs in these lncRNA genes with lung cancer were unknown. We conducted a case‐control study to address this issue.MethodsUsing the TaqMan method, we genotyped 17 SNPs located in the 13 lncR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Although these studies display downregulated expressions of circ‐SMARCA5 in some cancers, the involvement of circ‐SMARCA5 in lung cancer has not been clearly clarified, and only one study shows that circ‐SMARCA5 is downregulated in NSCLC tissues compared to the adjacent normal tissues, and it inhibits cell proliferation, migration as well as invasion in NSCLC cell lines . Some recent studies have implied that non‐coding RNAs, especially circRNAs, play crucial roles in pathology and progression of NSCLC . For example, long non‐coding RNA KDM5B anti‐sense RNA 1 enhances tumor progression in NSCLC; circular RNA F‐circSR derived from SLC34A2‐ROS1 fusion gene enhances cell migration in NSCLC; overexpression of circular RNA FARSA promotes NSCLC cell migration and invasion .…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies display downregulated expressions of circ‐SMARCA5 in some cancers, the involvement of circ‐SMARCA5 in lung cancer has not been clearly clarified, and only one study shows that circ‐SMARCA5 is downregulated in NSCLC tissues compared to the adjacent normal tissues, and it inhibits cell proliferation, migration as well as invasion in NSCLC cell lines . Some recent studies have implied that non‐coding RNAs, especially circRNAs, play crucial roles in pathology and progression of NSCLC . For example, long non‐coding RNA KDM5B anti‐sense RNA 1 enhances tumor progression in NSCLC; circular RNA F‐circSR derived from SLC34A2‐ROS1 fusion gene enhances cell migration in NSCLC; overexpression of circular RNA FARSA promotes NSCLC cell migration and invasion .…”
Section: Discussionmentioning
confidence: 99%
“…37,38 A pan-cancer analysis revealed that LINC01614 could be used as diagnostic/prognostic biomarkers for digestive systems, respiratory systems, head and neck cancers, and so forth. 39 Liu et al's 40 study revealed that rs3113503 in LINC01614 was significantly associated with the non-small cell lung cancer risk. However, to date, little research has been conducted on the association between the functional variants of LINC01614 and HNSCC risk, let alone the underlying mechanisms.…”
mentioning
confidence: 99%
“…Furthermore, SNPs can also affect functionality of long non-coding RNAs (lncRNAs), another group of regulatory RNAs that participate in chromatin modifications, transcription, and post-transcriptional processing. Notably, to date, 495,729 SNPs have been identified in human lncRNAs transcripts [175], with many of these mutations shown to affect lncRNA structure [176] or their interactions with miRNA [175,177,178]. The SNP-related impairment of lncRNA function is sometimes associated with human diseases including carcinogenesis and responses to chemotherapy [179][180][181][182].…”
Section: Snpsmentioning
confidence: 99%